IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN LINGKUNGAN DI PUSKESMAS KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Sri Wahyuni; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Health workers have an important role to improve the maximum quality of health services to the community so that the community is able to increase awareness, willingness, and ability to live a healthy life as referred to in the preamble to the 1945 Constitution of the Republic of Indonesia. The formulation of the problem from this research is the factors which affect the implementation of the Environmental Health Service policy at the Sentajo Raya Health Center, Kuantan Singingi Regency has not run optimally. The purpose of the study was to determine the factors that influence the implementation of the Environmental Health Service policy at the Sentajo Raya Public Health Center, Kuantan Singingi Regency in 2019. The method used in this study was descriptive qualitative. Based on the results of the study, it was shown that the Puskesmas Sentajo Raya at this time did not have environmental health workers. Ideally, with a large work area, it should be supported by the availability of health workers who can serve the community optimally. The health office and the Puskesmas in this case did not establish good communication causing the shortage of health workers needed by the community was not handled quickly then the socialization of the Ministerial Regulation at the Sentajo Raya District Health Center was not carried out optimally. Keywords: policy implementation, Regulation of the Minister of Health.